Greenhouse Gas Emission Reduction Strategies in the Transportation and Solid Waste Sector in Cilacap Regency - Nurandani Hardyanti; Budi Prasetyo Samadikun; Adinda Ragil Saputri; Adinda Putra Yuwono (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2022)
Every year, population growth in Cilacap Regency inevitably results in various impacts in various fields, including transportation and solid waste. The number of motorized vehicles in the Cilacap Regency has increased from 588,283 units in 2017 to 714,533 units in 2020. On the other hand, solid waste generation in Cilacap Regency in 2020 reached 0.22 tons per capita per year. Both activities can potentially reduce the air quality of the Cilacap Regency. One of the causes of the decline in air quality is CO2, CH4, and N2O gases, which can cause global warming. This study aims to inventory and project GHG emission loads, determine mitigation strategies and design regulations related to GHG emission reduction in the transportation and solid waste sector in Cilacap Regency. The method used to inventory GHG emissions in this research is the 2006 IPCC method with Tier 1 and Tier 2 accuracy. Then it is projected for the next ten years with a Business As Usual (BAU) scenario. To determine the selected reduction strategy using SWOT and QSPM analysis. The inventory results and projected GHG emissions in the solid waste sector in 2030 are 109.29 Gg CO2e. 4 GHG emission reduction programs in the solid waste sector could reduce up to 29.49% Gg CO2-e in 2030. Then the BAU scenario GHG emissions in the transportation sector in 2030 reached 21,417 Gg CO2e. The six proposed scenarios were able to produce a percentage of GHG reduction of 7 65% in 2030 or 1,638,409 Tons of CO2e or 1,638 Gg CO2e from 2021-to 2030 with a priority strategy for reducing GHG emissions is increasing pollution buffers by building green open space and non-motorized pathways with a reduced rate of 2%.